2017
DOI: 10.1177/0363546517712952
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Predictors of Clinical Outcomes After Revision Anterior Cruciate Ligament Reconstruction

Abstract: Background Revision anterior cruciate ligament (ACL) reconstruction has been documented to have worse outcomes compared with primary ACL reconstructions. The reasons why remain varied. The purpose of this study was to determine whether previous or current surgical factors noted at the time of revision ACL reconstruction are significant predictors towards activity level, sports function, and osteoarthritis (OA) symptoms at 2-year follow-up. Hypothesis Certain factors under the control of the surgeonat the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Despite a large body of the literature regarding single anterior cruciate ligament (ACL) graft failures, only a few studies emphasizing multiple ACL graft failures have been published [ 1 , 5 , 12 , 13 , 15 , 16 ]. Prior studies have shown that undergoing more than one revision ACL-R is a predictor for worse patient-reported outcomes (PROs) and subsequent graft failures [ 2 , 17 ]. Additionally, the majority of patients that have sustained multiple ACL graft failures present with meniscal tears and cartilage lesions [ 5 , 12 , 13 , 15 , 16 ], which are well-known negative predictors for long-term knee function.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a large body of the literature regarding single anterior cruciate ligament (ACL) graft failures, only a few studies emphasizing multiple ACL graft failures have been published [ 1 , 5 , 12 , 13 , 15 , 16 ]. Prior studies have shown that undergoing more than one revision ACL-R is a predictor for worse patient-reported outcomes (PROs) and subsequent graft failures [ 2 , 17 ]. Additionally, the majority of patients that have sustained multiple ACL graft failures present with meniscal tears and cartilage lesions [ 5 , 12 , 13 , 15 , 16 ], which are well-known negative predictors for long-term knee function.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing number of anterior cruciate ligament (ACL) reconstructions, the number of ACL revision surgeries has risen accordingly [1][2][3][4][5][6]. ACL surgery is a frequently Abstract Purpose To investigate the effect of tibial tunnel orientation on graft-bending angle and stress distribution in the ACL graft.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the MARS group age did not show any impact on clinical and functional outcome [ 2 ]. One reason might be the lower median age of 26 yrs.…”
Section: Discussionmentioning
confidence: 99%